2023
DOI: 10.1051/0004-6361/202346207
|View full text |Cite
|
Sign up to set email alerts
|

Using multiobjective optimization to reconstruct interferometric data. Part I

Abstract: Context. Imaging in radioastronomy is an ill-posed inverse problem. However, with increasing sensitivity and capabilities of telescopes, several strategies have been developed in order to solve this challenging problem. In particular, novel algorithms have recently been proposed using (constrained) nonlinear optimization and Bayesian inference. Aims. The Event Horizon Telescope (EHT) Collaboration convincingly investigated the fidelity of their image reconstructions with large surveys, solving the image recons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…α is the regularization parameter and R flux is a total flux constraint with a compact flux density f. In this framework, DoG-HiT reconstruction attempts to recover a total-intensity image while minimizing user-based choices, i.e., by using only data terms for the static total-intensity image that are robust against the self-calibration, and a data-driven choice of the regularization term. It has been demonstrated that EHT data are constraining enough for closure-only imaging of the totalintensity image (e.g.,Chael et al 2018; M87 * Paper IV; Paper III;Müller et al 2023). …”
mentioning
confidence: 99%
“…α is the regularization parameter and R flux is a total flux constraint with a compact flux density f. In this framework, DoG-HiT reconstruction attempts to recover a total-intensity image while minimizing user-based choices, i.e., by using only data terms for the static total-intensity image that are robust against the self-calibration, and a data-driven choice of the regularization term. It has been demonstrated that EHT data are constraining enough for closure-only imaging of the totalintensity image (e.g.,Chael et al 2018; M87 * Paper IV; Paper III;Müller et al 2023). …”
mentioning
confidence: 99%